(3QSGdI aj fjd eUQ hCgQGegGs - (3CMeO Hf YeGO Hf jhSa Hf YHO GdfHj, CHh GdYHGS, TgGH GdOjf GdCbagSj Ke GdbGgQj , GHf GdpYneGO ,J (B808 (3g` s
(3ChdgG (B:s
(3bGd QShd Gddg Udi Gddg Ydjg hSde (B( (3CQHYI dGJTHY ef CQHY Yjf ef fXQ hCKfi ef PcQ hCQV ef eWQ hYGde ef NHQ (B) s
(3BNQgG (B:s
(3Ef JMJ GdHMQ dfGQ hEf JMJ GdfGQ dHMQ Edi BNQ GdMOjK s
(3HgG fXGe GdJYbjHIs
(3fSNI KGfjIs
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B184 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B2 - (3U (B26s
Keywords: (3GdLZQGajG h GdHdOGfs